1999
DOI: 10.1128/jvi.73.4.2770-2780.1999
|View full text |Cite
|
Sign up to set email alerts
|

Activated Mouse Notch1 Transactivates Epstein-Barr Virus Nuclear Antigen 2-Regulated Viral Promoters

Abstract: Epstein-Barr virus nuclear antigen 2 (EBNA2) is essential for B-cell immortalization by EBV, most probably by its ability to transactivate a number of cellular and viral genes. EBNA2-responsive elements (EBNA2REs) have been identified in several EBNA2-regulated viral promoters, each of them carrying at least one RBP-Jκ recognition site. RBP-Jκ recruits EBNA2 to the EBNA2RE and, once complexed to EBNA2, is converted from a repressor into an activator. An activated form of the cellular receptor Notch also intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 72 publications
1
12
2
Order By: Relevance
“…These data indicate that in HEK293 cells, both RBP-Jκ sites are important for LMP2A auto-regulation. This is in contrast to previous data which demonstrates that the second RBP--IC to activate the minimal LMP2A promoter in B cells (Hofelmayr et al, 1999) and is likely due to the differences in cell types and promoter constructs used.…”
Section: Analysis Of the Requirement For Rbp-jκ Sites In Lmp2a Auto-rcontrasting
confidence: 99%
See 3 more Smart Citations
“…These data indicate that in HEK293 cells, both RBP-Jκ sites are important for LMP2A auto-regulation. This is in contrast to previous data which demonstrates that the second RBP--IC to activate the minimal LMP2A promoter in B cells (Hofelmayr et al, 1999) and is likely due to the differences in cell types and promoter constructs used.…”
Section: Analysis Of the Requirement For Rbp-jκ Sites In Lmp2a Auto-rcontrasting
confidence: 99%
“…These results demonstrate that LMP2A activates the Notch pathway in both B cells and epithelial cells, and exploits this pathway to regulate its own expression. Other groups have shown that Notch-IC can activate EBNA2 responsive promoters, including that of LMP2A, and gel shift analysis has demonstrated that Notch-IC can bind to RBP-Jκ sites in the LMP2A promoter (Hofelmayr et al, 1999). That LMP2A can activate the Notch pathway in vivo provides the missing link in an auto-regulatory loop.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It then recruits EBNA2 to activate transcription via its acidic transactivating domain. In fact an activated version of the mouse Notch1 can induce the expression of EBNA2 targets Viruses and cancer which confirms that EBNA2 makes use of the physiological Notch pathway to activate its targets (Hofelmayr et al 1999;Strobl et al 2000). The PU.1 protein, another DNA binding protein has also been suggested to interact with EBNA2 to activate transcription in EBNA2 responsive promoters (Sjoblom et al 1995).…”
Section: Ebv-mediated Immortalizationmentioning
confidence: 91%